Contribution of Seaweed Cultivation (E. Cottonii) to Household Income in Punaga Village, Laikang District, Takalar Regency - Arum Faindah; Benny Audy Jaya Gosari; Abdul Wahid; Andi Amri; Sulaiman Gosalam; Esther Sanda Manapa (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2026)
The cultivation of cottoni seaweed (E. cottonii) in Punaga Village, Laikang District, Takalar Regency has great potential as the main livelihood of coastal communities. However, the extent to which this business contributes to household income still needs to be analyzed empirically, given the existence of other sources of income such as fishing and teaching. This study aims to analyze the total household income of seaweed farmers (E. cottonii) and the contribution of seaweed cultivation (E. cottonii) to household income. This study was conducted in October-November 2025 in Punaga Village, Laikang District, Takalar Regency, using a quantitative descriptive approach. A total of 50 respondents were selected from a population of 729 seaweed farmers using stratified random sampling based on five hamlets. Primary data collection was conducted through questionnaires, in-depth interviews, direct observation, and documentation, while secondary data was analyzed using total cost, total income, income analysis, household income, and contribution formulas. The results of the study show that the average income from E. cottonii seaweed cultivation 2.875.304.617. This income contributes the most to the total household income of 4.428.343.606, with a contribution percentage of 65% and is classified as large. In addition to income from seaweed cultivation, other sources of household income come from fishing activities amounting to IDR 1.195.115.997, income as teachers amounting to IDR 242.197.992, income from wives amounting to IDR 84.525,000, and income from children amounting to IDR 31.515,000. These findings indicate that seaweed cultivation plays a strategic role in supporting the household economy.